A Comparative Analysis of the Financial Stability of Islamic and Conventional Banks: Evidence from 10 Countries - Bundhoo, Mohammad Naweed (2013)
Half a decade since the unfolding of the Global Financial Crisis (GFC), the global economic scene is yet fogged by a steady and spreading financial gloominess. No countries are left unscratched. The financial sector has received a heavy blow. Islamic banking and finance industry, one of the most fast-paced booming sector of the worldwide financing system, has become pervasively distinguished and too big to be ignored. This study attempts to address the financial stability of Islamic banks and conventional banks. The level of bank stability is measured individually using one of accounting-based bank soundness measurement called the Z-score indicator. This paper uses secondary financial data of 71 Islamic banks and 92 conventional banks from 2005-2011 covering ten countries. The econometric model is regressed based on panel data analysis and robust estimation technique. The first hand data analysis show Islamic banks are more financially stable than conventional banks. The empirical findings do not provide a clear cut answer on the stability of Islamic banks.